Cairo in the War 1939-1945 - Cooper, Artemis 1953- (Penguin, 1995)
For troops in the desert, Cairo meant fleshpots or brass hats. For well-connected officers, it meant polo at the Gezira Club and drinks at Shepheard's. For the irregular warriors, Cairo was a city to throw legendary parties before the next mission behind enemy lines. For countless refugees, it was a stopping place in the long struggle home. The political scene was dominated by the British Ambassador Sir Miles Lampson. In February 1942 he surrounded the Abdin Palace with tanks and attempted to depose King Farouk. Five months later it looked as if the British would be thrown out of Egypt for good. Rommel's forces were only sixty miles from Alexandria - but the Germans were pushed back and Cairo life went on. Meanwhile, in the Egyptian Army, a handful of young officers were thinking dangerous thoughts